When data contradict statiscal predictions: cases of successful school performance among underprivileged strata - Zago, Nadir (Paidéia (Ribeirão Preto), 2000)
How can we explain situations of clear evidence of successful school performance when the social and cultural reality of the students is unfavorable to their school education? Without intending to answer this question, in this study we present some research data concerning underprivileged families who experienced situations demonstrating school adaptation and a longer prermancen of their children in the school system compared to the statistical data about the Brazilian educational reality. Going against the generic pathology-creating vision of underprivileged families, the study shows the error we incur when we base ourselves on middle class standards to evaluate the practices observed in socially underprivileged classes.